PARADIGMA DAN REKAYASA SOSIAL DAKWAH MAJELIS TABLIGH AISYIYAH KOTA PEKALONGAN - Khaerunnisa Tri Darmaningrum (J-MD Jurnal Manajemen Dakwah, 2021)
The Tabligh Aisyiyah Assembly was established on May 19, 1917. Previously, the initial form of Aisyiyah was the Sopo Tresno association in 1914. It started with a meeting at the house of KH Ahmad Dahlan in 1917, which Aisyiyah later founded. The purpose of establishing a tabligh assembly is not only to preach but to help the people around them. Of course, in an organization there are several divisions to make it easier to achieve goals. As for the Tabligh Aisyiyah Assembly, all people from junior high school age and equivalent can be participated in for life. In a sense, when you enter Aisyiyah, you must be ready to serve in it. Likewise, Aisyiyah has 4 divisions where each division has its own duties. Keywords: assembly, paradigm, Tabligh